Loss of endothelial barrier in Marfan mice (mgR/mgR) results in severe inflammation after adenoviral gene therapy - Seppelt, Philipp; Schwill, Simon; Weymann, Alexander; Arif, Rawa; Weber, Antje; Zaradzki, Marcin; Richter, Karsten; Wagner, Andreas H.; Karck, Matthias; Kallenbach, Klaus (PLOS ONE, 2016)
Objectives Marfan syndrome is an autosomal dominant inherited disorder of connective tissue. The vascular complications of Marfan syndrome have the biggest impact on life expectancy. The aorta of Marfan patients reveals degradation of elastin layers caused by increased proteolytic activity of matrix metalloproteinases (MMPs). In this study we performed adenoviral gene transfer of human tissue inhibitor of matrix metalloproteinases-1 (hTIMP-1) in aortic grafts of fibrillin-1 deficient Marfan mice (mgR/mgR) in order to reduce elastolysis. Methods We performed heterotopic infrarenal transplantation of the thoracic aorta in female mice (n = 7 per group). Before implantation, mgR/mgR and wild-type aortas (WT, C57BL/6) were transduced ex vivo with an adenoviral vector coding for human TIMP-1 (Ad.hTIMP-1) or β-galactosidase (Ad.β-Gal). As control mgR/mgR and wild-type aortas received no gene therapy. Thirty days after surgery, overexpression of the transgene was assessed by immunohistochemistry (IHC) and collagen in situ zymography. Histologic staining was performed to investigate inflammation, the neointimal index (NI), and elastin breaks. Endothelial barrier function of native not virus-exposed aortas was evaluated by perfusion of fluorescent albumin and examinations of virus-exposed tissue were performed by transmission electron microscopy (TEM). Results IHC and ISZ revealed sufficient expression of the transgene. Severe cellular inflammation and intima hyperplasia were seen only in adenovirus treated mgR/mgR aortas (Ad.β-Gal, Ad.hTIMP-1 NI: 0.23; 0.43), but not in native and Ad.hTIMP-1 treated WT (NI: 0.01; 0.00). Compared to native mgR/mgR and Ad.hTIMP-1 treated WT aorta, the NI is highly significant greater in Ad.hTIMP-1 transduced mgR/mgR aorta (p = 0.001; p = 0.001). As expected, untreated Marfan grafts showed significant more elastolysis compared to WT (p = 0.001). However, elastolysis in Marfan aortas was not reduced by adenoviral overexpression of hTIMP-1 (compared to untreated Marfan aorta: Ad.hTIMP-1 p = 0.902; control Ad.β-Gal. p = 0.165). The virus-untreated and not transplanted mgR/mgR aorta revealed a significant increase of albumin diffusion through the endothelial barrier (p = 0.037). TEM analysis of adenovirus-exposed mgR/mgR aortas displayed disruption of the basement membrane and basolateral space. Conclusions Murine Marfan aortic grafts developed severe inflammation after adenoviral contact. We demonstrated that fibrillin-1 deficiency is associated with relevant dysfunction of the endothelial barrier that enables adenovirus to induce vessel-harming inflammation. Endothelial dysfunction may play a pivotal role in the development of the vascular phenotype of Marfan syndrome.